Linezolid: A Strategic Approach to Antimicrobial Therapy - Shruti Vimal; Shradha Yadav; Madhura Bhosle (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Linezolid is a synthetic antibiotic that is used for the treatment of infections caused by aerobic Gram-positive bacteria. Its effects are bacteriostatic against both enterococci and staphylococci and bactericidal against most isolates of streptococci. It exerts its antibacterial activity by inhibiting the initiation of bacterial protein synthesis—more specifically, it binds to the 23S ribosomal RNA of the 50S subunit and prevents the formation of the 70S initiation complex which is essential for bacterial reproduction. We present here a case report of a 70-year-old female patient with a known case of diabetes mellitus (DM) with scleroderma and diagnosed with bilateral (BL) metastatic carcinoma breast. The patient had developed a shoulder abscess which was positive for methicillin-sensitive Staphylococcus aureus for which she was prescribed linezolid and had various manifestations which are being discussed here.